KEPUASAN SEBAGAI VARIABEL ANTARA KUALITAS PRODUK, KUALITAS PELAYANAN, DAN PERSEPSI NILAI TERHADAP LOYALITAS KONSUMEN PADA RESTORAN BARU - Ramdhani, Husein Slamet; Daryanto, Arief; Rifin, Amzu (Jurnal Ilmu Keluarga dan Konsumen, 2015)
In consumer behavior study, customer satisfaction and loyalty are important aspects that determine the sustainability of the business. Especially in new business that has a considerable number of competitors. Therefore, a product quality and services quality that can increase positive value of consumer are needed. This study aimed to analyze the effect of product quality, service quality, and perceived value that was mediated by satisfaction to customer loyalty in the new restaurant. The study involved 140 consumers at least once make a purchase in Durian Soup XYZ Restaurant that was located at Bogor. Perceived value was measured by the Likert scale. Data were collected by questionnaires and analyzed by Structural Equation Modeling (SEM). The resultsshowed that the quality of the product and the perceived value had significant positive relationship with consumer satisfaction. In addition, customer satisfaction also had a significant positive relationship with customer loyalty. This finding suggests for new restaurant to maintain product quality and to build positive value among consumer so will increase consumer satisfaction that will lead into consumer loyalty.